Environmental, spatial and phylogenetic determinants of fish life‐history traits and functional composition of Australian rivers. (27th May 2013) - Sternberg, David; Kennard, Mark J.
Summary The biogeography of freshwater fish is determined in part by large‐scale filters such as phylogenetic history, the spatial arrangement of catchments and environmental variability. Species are filtered from the regional pool if they possess a combination of functional traits enabling them to persist in the local environment. This article aims to quantify the relative importance of these large‐scale filters in determining spatial variation in freshwater fish life‐history traits and functional trait composition of Australian river basins. We developed a database of 10 life‐history traits for 141 native freshwater fish species and compiled species distribution data for 123 river basins across the Australian continent. In order to partition the variation in the representation of life‐history trait into unique and overlapping components, we also quantified the degree of phylogenetic relatedness among species, the geographical arrangement of river basins throughout the landscape and 12 broad‐scale environmental factors. We then related life‐history trait composition to gradients of environmental variation by constrained multivariate ordination and simple linear regression. Our explanatory matrices accounted for 86.8% of the total variation in life‐history trait composition at the river basin scale, of which 59.4% could be attributed to phylogeny and spatially structured environmental variation. This component represents the overlap among the broad‐scale filtering processes of phylogenetic history, spatial autocorrelation and environmental variability in accounting for the distribution of life‐history traits across Australian river basins. Our analysis showed strong associations between suites of life‐history traits that define generation time and reproductive output and a strong climate–hydrological gradient across the landscape. We also showed significant correlations between specific environmental variables and a number of key life‐history traits that highlight the importance of trait‐mediated environmental filters at broad spatial scales. This study advances our conceptual understanding of broad‐scale community assembly theory and has revealed trait–environment relationships at scales relevant to restoration and conservation of aquatic biodiversity. Our study provides greater insight into the determinants of spatial variation in fish species distributions and potentially addresses key scientific challenges, such as understanding how fish communities are assembled, and identifies the potential threats to, and responses of, these communities caused by environmental change.